Microstructural effect on the corrosion behavior of n- and p-type bismuth tellurides fabricated by induction melting - Farah M. El-Makaty (14157090) (2023)
Numerous efforts have been made to understand and enhance the thermoelectric properties of bismuth telluride alloys. However, limited studies have been reported to investigate the corrosion behavior of these alloys and their suitability for industrial applications. This paper examines the corrosion behavior of three different bismuth telluride alloys prepared by induction melting: pristine Bi2Te3, n-type Bi2Te2.55Se0.45, and p-type Bi0.6Sb1.4Te3. The electrochemical response of the samples is tested in 3.5 wt% NaCl solution at room temperature. Potentiodynamic polarization curves (Tafel plots) revealed that the n-type sample formed a passive layer compared to the pristine and the p-type samples, which showed pitting corrosion. The different trends observed in the samples were related to their evolved microstructures, where fingerprint-like features in the pristine and the p-type samples showed high susceptibility to pitting corrosion. In contrast, a unique needle-like microstructure of the n-type samples acted as nucleation sites for passive layer formation causing higher corrosion resistance in this sample. Other Information Published in: Materials Characterization License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matchar.2023.112987